2014
DOI: 10.1371/journal.pone.0098038
|View full text |Cite
|
Sign up to set email alerts
|

Improved Testing of Recent HIV-1 Infections with the BioRad Avidity Assay Compared to the Limiting Antigen Avidity Assay and BED Capture Enzyme Immunoassay: Evaluation Using Reference Sample Panels from the German Seroconverter Cohort

Abstract: BackgroundThe variety and limitations of current laboratory methods for estimating HIV-incidence has driven attempts to improve and standardize the performance of serological ‘Tests for Recent HIV-Infections’ (TRI). Primary and follow-up HIV-1 positive plasma samples from individuals with well-defined dates of infection collected as part of the German Seroconverter Cohort provided specimens highly suitable for use in comparing the performance of three TRIs: the AWARE™ BED™ EIA HIV-1 Incidence test (BED-CEIA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 43 publications
1
23
1
Order By: Relevance
“…The discordance between the SAM and the BED-CEIA was caused mainly by a recent result with the SAM and a nonrecent result with the BED-CEIA, which is also in agreement with the related study (15). Referring to previously published data (2,24,25) and our subset analyses, the BED-CEIA yields significantly higher accuracy and a lower false recency rate than the SAM and the multianalyte algorithm that includes the SAM. Moreover, with the SAM, the probability of a sample being classified as recent showed a broad distribution over the duration of infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The discordance between the SAM and the BED-CEIA was caused mainly by a recent result with the SAM and a nonrecent result with the BED-CEIA, which is also in agreement with the related study (15). Referring to previously published data (2,24,25) and our subset analyses, the BED-CEIA yields significantly higher accuracy and a lower false recency rate than the SAM and the multianalyte algorithm that includes the SAM. Moreover, with the SAM, the probability of a sample being classified as recent showed a broad distribution over the duration of infection.…”
Section: Discussionsupporting
confidence: 89%
“…However, the SAM achieved a lower accuracy than serological HIV-1 incidence assays (2,3,24,25) and demonstrated an inconveniently broad distribution of individual durations of recency. Moreover, the SAM would not be cost-effective if HIV-1 genotyping was performed solely for cross-sectional surveys to estimate HIV-1 incidence.…”
Section: Discussionmentioning
confidence: 92%
“…These three patients comprised of different subtypes (B, A and CRF-02 AG) and all had a viral load <50 copies/ml. Studies have shown that subtype A and/or low viral load can be contributing factors that result in false recent AI in established infections (Laeyendecker et al, 2012;Hauser et al, 2014;Kassanjee et al, 2014). The FRR of our assay at less than 1% is one of the lowest described for HIV Incidence assays (Suligoi et al, 2002;Doung et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Based on combined assessment of retrospective and prospective HIV samples, the FRR of the assay is 0.89% (95% CI: 0.24-2.3%). Low CD4 count, antiretroviral therapy, AIDS-defining illness, elite controllers, undetectable viral load and HIV subtypes can influence the FRR of incidence assays (Chawla et al, 2007;Selleri et al, 2007;Re et al, 2010;Poropatich and Sullivan, 2011;Chaillon et al, 2012;Laeyendecker et al, 2012;Hauser et al, 2014). Only three longstanding HIV infected patients from the retrospective study had a low AI.…”
Section: Discussionmentioning
confidence: 97%
“…The greater the proportion of high avidity antibodies remaining bound increases the avidity index, therefore indicating established (long term) infection (Suligoi et al, 2002). The Bio-Rad Avidity EIA is a modification of the GS HIV-1/HIV-2 Plus O EIA (Redmond, MA) (Hauser et al, 2014). This assay uses 0.1M diethylamine (DEA) to dissociate low avidity antibodies characteristic of recent infection.…”
Section: Methods Of Measuring Hiv Incidencementioning
confidence: 99%